Inflammatory links between epilepsy and depression: a review of mechanisms and therapeutic strategies - Yu-Qian Shi; He-Cai Yang; Cong He; Yu-Hao Wang; Jia Zheng; Xing-Yi Wang; Fang-Yi Hao; Chu-Wen Feng; Lin Ma; Yue-Hui Zhang; Zheng Liu (Frontiers in Neuroscience)
Depression is the most common psychiatric comorbidity of epilepsy. While antiseizure medications (ASMs) can exacerbate depressive symptoms, depression itself may increase both the frequency and duration of epileptic seizures. The pathophysiological mechanisms underlying epilepsy-depression comorbidity (EDC) involve neurotransmitter imbalance, inflammatory responses, oxidative stress (OS), gut microbiota dysbiosis, and neuroendocrine abnormalities. Recent studies highlight that inflammation contributes to EDC via multiple interconnected mechanisms, including glial cell activation, cytokine release, pyroptosis, and oxidative damage, ultimately leading to synaptic dysfunction and neuroimmune imbalance. Drawing from representative and recent evidence, this review summarizes the role of inflammation in the pathogenesis and progression of EDC. It also outlines current inflammation-targeted therapeutic strategies, such as anti-inflammatory drugs, antioxidants, herbal medicine, acupuncture, probiotic modulation, and precision therapies. This review provides a conceptual framework for understanding inflammation-mediated EDC and offers insights into targeted treatment approaches.